2008
DOI: 10.2969/jmsj/06020495
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of the Shestakov-Umirbaev inequality

Abstract: We give a generalization of the Shestakov-Umirbaev inequality which plays an important role in their solution of the Tame Generators Problem on the automorphism group of a polynomial ring. As an application, we give a new necessary condition for endomorphisms of a polynomial ring to be invertible, which implies Jung's theorem in case of two variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…The inequality of Shestakov and Umirbaev used in this proof has recently been generalized by both Kuroda [14] and Vénéreau [21]. Each obtains the original inequality as a corollary, avoiding the * -reduced pair condition used by Shestakov and Umirbaev.…”
Section: Applying the Inequality Of Shestakov And Umirbaevmentioning
confidence: 89%
“…The inequality of Shestakov and Umirbaev used in this proof has recently been generalized by both Kuroda [14] and Vénéreau [21]. Each obtains the original inequality as a corollary, avoiding the * -reduced pair condition used by Shestakov and Umirbaev.…”
Section: Applying the Inequality Of Shestakov And Umirbaevmentioning
confidence: 89%
“…Then, due to [9, Theorem 3] (see also [5], [7] and [11]), it follows that Recently, the author [6] showed that no tame automorphism of k[x] for n = 3 admits a reduction of type IV.…”
Section: Question 41mentioning
confidence: 99%
“…To prove Theorem 1.9, we use the generalized Shestakov-Umirbaev theory [12], [13]. For the convenience of the reader, we give a short introduction to this theory.…”
Section: Shestakov-umirbaev Reductionsmentioning
confidence: 99%
“…By definition, we have deg w f 3 = w 3 and f w 3 = αx 3 + p ′ for such F , where p ′ := p w if deg w p = w 3 , and p ′ := 0 otherwise. Recently, the author [12], [13] generalized the Shestakov-Umirbaev theory. By means of this theory, we prove the following theorem in Section 9.…”
Section: Introductionmentioning
confidence: 99%